Modelo espacial para estudiar la distribución del monto del gasto devengado de la inversión pública a nivel provincial en el Perú - Ocola Aguero, Kendy Brigitte (2024)
This thesis presents a detailed and technical exploration of the Conditional Autoregressive (CAR) and Simultaneous Autoregressive (SAR) spatial models to analyze the data on public investment from the year 2022, specifically to study the spatial distribution of accrued expenditure in public investment in Peru. Through a combination of theoretical analysis and simulations, the research establishes methodologies to evaluate how variables such as corruption, levels of local government investment, prioritized portfolio, and physical progress of the investment influence the accrued expenditure in different provinces. This study significantly contributes to the understanding of the spatial distribution of public spending and the factors that affect it, using advanced statistical techniques to improve the accuracy and effectiveness of the estimates of the models used. The results of the analysis provide critical perspectives on the management and allocation of public funds, offering a valuable tool for planners and policymakers in public policy formulation.